Ultrasonic transducer based on beta-PVDF for fluidic microagitation in a lab-on-a-chip device - Cardoso, V. F. (2009)
This paper describes a fully-integrated lab-on-a-chip device for testing and monitoring biochemical parameters in biological fluids. The major innovation of this microdevice is the application of an acoustic microagitation technique with automatic electronic control based on a β-PVDF piezoelectric polymer placed underneath the microfluidic structures. Experimental results regarding the influence of the thickness of the polymer on the reaction rate of biological fluids are presented. Moreover, the study of the transmittance curve of β-PVDF with transparent conductive electrodes is also presented. Transparent electrodes are a constraint once the polymer is incorporate underneath the reaction chamber due to the analytical measurement by spectrophotometry.